The Cytoprotective Role of Antioxidants in Mammalian Cells Under Rapidly Varying UV Conditions During Stratospheric Balloon Campaign - Przystupski, Dawid; Górska, Agata; Rozborska, Paulina; Bartosik, Weronika; Michel, Olga; Rossowska, Joanna; Szewczyk, Anna; Drąg-Zalesińska, Małgorzata; Kasperkiewicz, Paulina; Górski, Jędrzej; Kulbacka, Julita (Frontiers in Pharmacology, 2019)
The current age of dynamic development of the space industry brings the mankind closer to routine manned space flights and space tourism. This progress leads to a demand for intensive astrobiological research aimed at improving strategies of the pharmacological protection of the human cells against extreme conditions. Although routine research in space remains out of our reach, it is worth noticing that the unique severe environment of the Earth’s stratosphere has been found to mimic subcosmic conditions, giving rise to the opportunity to use the stratospheric surface as a research model for the astrobiological studies. Our study included launching into the stratosphere a balloon containing mammalian normal and cancer cells treated with various compounds to examine whether these substances are capable of protecting the cells against stress caused by rapidly varying temperature, pressure and radiation, especially UV. Due to oxidative stress caused by irradiation and temperature shock, we used natural compounds which display antioxidant properties, namely - catechin isolated from green tea, honokiol derived from magnolia, curcumin from turmeric and cinnamon extract. “After-flight” laboratory tests have shown the most active antioxidants as potential agents which can minimize harmful impact of extreme conditions on human cells.